Assessment of functional conditions of basketball and football players during the load by applying the model of integrated evaluation - Zumbakyte-Sermuksniene, R.; Kajeniene, A.; Vainoras, A.; Berskiene, K.; Augutiene, V. (Medicina, 2010)
We consider the human body as an adaptable, complex, and dynamic system capable of organizing itself, though there is none, the only one, factor inside the system capable of doing this job. Making use of the computerized ECG analysis system "Kaunas-load" with parallel registration of ECG carrying out body motor characteristics, ABP, or other processes characterizing hemodynamics enable one to reveal and evaluate the synergistic aspects of essential systems of the human body what particularly extends the possibilities of functional diagnostics. The aim of the study was to determine the features of alterations in the functional condition of basketball and football players and nonathletes during the bicycle ergometry test by applying the model of evaluation of the functional condition of the human body. Material and methods. The study population consisted of 266 healthy athletes and nonathletes. Groups of male basketball players, male football players, male nonathletes, female basketball players, and female nonathletes were studied. A computerized ECG analysis system "Kaunas-load" that is capable of both registering and analyzing the power developed by the subject and 12-lead ECG synchronically were used for evaluating the functional condition of the CVS. The subject did a computer-based bicycle ergometry test. The following ECG parameters at rest and throughout the load - HR, JT interval, and the deduced JT/RR ratio index that reflects the condition between regulatory and supplying systems - were evaluated. After measuring ABP, the pulse amplitude (S-D) was evaluated. The pulse blood pressure ratio amplitude (S-D)/S that depicts the connection between the periphery and regulatory systems was also evaluated. Speeds of changes in physiological parameters during physical load were evaluated too. Results. Heart rate and JT/RR ratio of athletes at the rest and during load were lower, and JT interval of rest was longer and became shorter more slowly during load, compared to that of healthy nonathletes. The pulse arterial blood pressure amplitude of men at rest and during load was higher than that of women. The pulse ABP amplitude of athletes was higher than that of nonathletes. The relative pulse ABP amplitude in the state of rest in the groups of men was higher than in groups of women. The relative pulse amplitude of female basketball players at rest and during load was higher than that of female nonathletes. Significant differences in the dynamics of speed of changes in HR, the pulse ABP amplitude, and the relative pulse ABP amplitude of male and female basketball players, male football players, as well as male and female nonathletes were observed. Conclusions. The newly deduced parameters, namely, speeds of changes in the parameters with changes in the phase of the load reflect very well peculiarities of functional condition of the human body during bicycle ergometry test. The sum total of those newly deduced parameters and customary parameters reveals new functional peculiarities of the human body.